ANALISIS MAJAS PADA LIRIK LAGU TULUS YANG BERJUDUL PAMIT DAN SEPATU - Salma Muamanah; Lastri Lastri; Nofiyanti Nofiyanti (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
Researchers are interested in researching the majas in song lyrics, because among the genres of literary works, the lyrics of the songs have the most typical language use such as poetry. The purpose of this study is to find out which majas are used in songs that are sought by sincere. This research uses qualitative descriptive method and the technique used in data collection technique is the sampling technique of puposive (random), and analyzed based on Gorys Keraf theory. the results of the analysis of the song lyrics on the song farewell and shoes Tulus, found rhetorical majas and figurative majors on the collection of song lyrics. Researchers also found the figurative majors contained in the collection of song lyrics can be grouped by vehicle and tenor.